Quality Of Frozen Cement From Landrace Boars In Modified Citrate Diluents With Different Glycerol Concentrations - Yohanes Paulus Martinus Bay; Thomas Mata Hine; Yustiany Yuliani Bette; W. Marlene Nalley (Journal of Innovative and Creativity, 2025)
The purpose of this study was to determine the quality of frozen semen from landrace boars in modified citrate diluents with different glycerol concentrations. The research material used was fresh cement from 2-3 year old landrace boar studs from 4 boars. This study used an experimental study with a completely randomized design method consisting of 4 treatments and 4 replications. The treatments in question are T1: S-KT + G 3%, T2: S-KT + G 5%, T3: S-KT + G 7% and T4: S-KT + G 9%. The diluted cement was stored at room temperature (27-28℃) for two hours (holding time), then centrifuged at 3000 RPM for 15 minutes. After centrifugation, the supernatant was discarded and the centrifuged pellet was re-diluted with basic diluent. The diluted semen was packed in 0.5 Ml straws, then packed, arranged in a freezing rack, and then equilibrated at 3-5℃ for 2 hours. Then the straws were frozen above the surface of liquid N2 with a distance of 10 cm at a temperature of ±-110℃ for 10 minutes. The results of this study indicate that the addition of different glycerols did not have a significant effect (P>0.05) on the motility, viability, abnormality and recovery rate of spermatozoa. It was concluded that the addition of different glycerols had the same impact but were not suitable for IB.